0382 CBT for Perinatal Insomnia - Postpartum Outcome. (12th April 2019) - Manber, Rachel; Bei, Bei; Rangel, Elizabeth; Simpson, Norah; Asarnow, Lauren
Abstract: Introduction: Insomnia during pregnancy is a risk for sleep challenges during the postpartum periods, when nighttime awakenings related to infant care is common and may be prolonged by insomnia. We present postpartum results from an RCT of CBT for insomnia (CBTI) among pregnant women. We hypothesize that better response to treatment during pregnancy would result in lower insomnia severity during the postpartum period. Methods: Pregnant women (N=179) meeting DSM-5 criteria for Insomnia Disorder, with duration criterion relaxed to one month, were randomized to five weekly sessions of CBTI or an active control (CTRL) therapy during pregnancy plus session at 6 weeks postpartum. Participants were excluded if they used prescription medications that could impact sleep or mood. The Insomnia Severity Index (ISI) was administered at 8, 18, and 30 weeks postpartum. Included in the analyses were 117 women (62 in CBTI; 55 in CTRL) who provided data for at least one of three postpartum assessments. At study entry, the mean maternal and gestation ages were 33.5 (SD 5.1) years and 24.7 (SD 5.1) weeks respectively. Thirty percent of the participants indicated Hispanic ethnicity. Results: Piecewise mixed effects models revealed that higher ISI at the end of pregnancy predicted higher overall ISI during the postpartum (p=.0001). Two distinct trajectories of postpartum ISI scores were observed (a) among CBTI participants who had at least 50% reduction in ISI during pregnancy (CBTI responders), mean ISI scores at the three postpartum time-points were below 6; (b) among CBTI participants with lower reduction in ISI during pregnancy (non-responders) and those assigned to the CTRL group, ISI scores during the postpartum were either variable (unstable) or elevated. The percentages of responders during pregnancy were 58.1% in CBTI and 17.0% in CTRL. Conclusion: We have previously reported that CBTI is effective in treating insomnia during pregnancy in the same study. Our current findings extend the benefits of CBTI for perinatal insomnia into at least 4.5 months postpartum. Importantly, good response to CBTI during pregnancy resulted in consistently low insomnia symptom severity during the postpartum period. Support (If Any): NIH: R01 NR013662